The influence of cue unreliability on judgment in a multiple cue probability learning task - York, Kenneth M; Doherty, Michael E; Kamouri, Joseph (Organizational behavior and human decision processes, 1987)
The effect of cue reliability was tested in a two-cue multiple-cue probability learning (MCPL) task. Subjects were 42 undergraduates. The cue validities were.78 and.37. Unreliability in a cue was defined as variability in multiple observations of that cue on a given trial. That variability was provided by adding random errors to the true value of the cue. One group was given consistent cues (i.e., the more valid cue was the more reliable cue), one group was given inconsistent cues, and the control group was given true scores. Cue reliability did not affect subjects' consistency or achievement, but did interact with the presence of outcome feedback. The subjective weights showed that subjects thought they weighted the more reliable cue more heavily regardless of the cue validities or their actual cue weightings. There were wide individual differences in performance, illustrating the need for an idiographic-statistical approach in studying decision making.